Immunohistochemical studies on duodenum, spleen and liver in mice: Distribution of ferroportin and prohepcidin in an inflammation model - D'anna, Maria Cecilia (2011)
Duodenum, spleen and liver have a crucial role in iron balance on the whole organism and are the major sites of Ferroportin (FPN) expression. Specific regulations between FPN and hepcidin are responsible for changes seen in physiopathological conditions such as inflammation. We studied in vivo effects of turpentine oil-induced acute inflammation on FPN expression, and its relation with prohepcidin and iron mobilization. Immunohistochemical procedures were performed using rabbit anti-mouse FPN and prohepcidin antibodies with goat-labeled polymer-HRP anti-rabbit (DAB) as secondary antibody. Plasma and tissular iron were also studied. Our results showed a notable expression and redistribution of duodenal FPN to basolateral membrane in turpentine-treated mice, compared with supranuclear and the weak basolateral expression observed in healthy mice. Red pulp macrophages of healthy mice showed FPN-hemosiderin co-localization, compared with turpentine-treated mice which showed lack of FPN. In liver of healthy mice, FPN was seen in Kupffer cells, whereas in turpentine-treated mice decreased. In addition, we observed an increment of hepatic prohepcidin with a significant hypoferremia. Our findings demonstrated that acute inflammation induced a differential distribution of FPN, showing a cell type specific response. In macrophages, increased hepatic prohepcidin induced degradation of FPN, resulting in hypoferremia. In enterocytes, the redistribution observed of duodenal FPN reflects a different regulation in this tissue. The observed response of the proteins studied may be part of a cyclical pattern of systemic effects of acute inflammation on mouse tissue.